2021
DOI: 10.1108/jkm-11-2020-0814
|View full text |Cite
|
Sign up to set email alerts
|

Global ranking of knowledge management and intellectual capital academic journals: a 2021 update

Abstract: Purpose The purpose of this study is to update a global ranking list of 28 knowledge management and intellectual capital (KM/IC) academic journals. The list should be periodically updated because the pool of active KM/IC researchers changes, researchers adjust their journal perceptions, citation indices change and new journals appear while others become discontinued. Design/methodology/approach The ranking list was created based on a survey of 463 active KM/IC researchers and journal citation impact metrics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 77 publications
0
11
0
1
Order By: Relevance
“…Concerning the journals publishing on phronesis in knowledge management, the most relevant journal in the field (Serenko and Bontis, 2021), i.e. the Journal of Knowledge Management (9), is the second in the ranking of publications.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…Concerning the journals publishing on phronesis in knowledge management, the most relevant journal in the field (Serenko and Bontis, 2021), i.e. the Journal of Knowledge Management (9), is the second in the ranking of publications.…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…The criteria included as follows: Peer-reviewed articles; Published in the top relevant KM journals (Serenko and Bontis, 2013, 2017, 2021); and From the launch of the journals until January 2020, when this SLR was conducted. …”
Section: Methodsmentioning
confidence: 99%
“…The second limitation is associated with the scoping of the review. To assure the quality of the findings, we used the relevant literature (Heisig and Kannan, 2020), including in the review the articles published in the top seven KM/IC journals (ranked Aþ or A in Serenko and Bontis, 2021). Therefore, important contributions from other KM journals, conference papers, books and professional reports may have been excluded.…”
Section: Conclusion Limitations and Future Studiesmentioning
confidence: 99%
“…Related to the primary research areas, they concluded that "there was an increase in KM as a primary research area from 24 to 36%". In 2020, Serenko and Bontis (2021) repeated their global ranking for 28 KM/IC academic journals. According to 463 responses of experts, they claimed that "Compared to the previous ranking study, fewer responders indicated KM as their primary and secondary research areas, while there was a slight increase in the number of scholars focusing on computer science/information technology/ information systems/library and information science (CS/IT/IS/LIS), informatics, accounting and finance and IC".…”
Section: Wisdom In the Km Literaturementioning
confidence: 99%
“…467–487; Jashapara, 2004, pp. 14–41; Jennex, 2017; Jennex and Bartczak, 2013; Serenko, 2013, 2021; Serenko and Bontis, 2017, 2021; Skyrme, 2003). This was a surprising finding because the key concepts of wisdom ( episteme , techne , phronesis , data, information, knowledge, knowing, etc.)…”
Section: Introductionmentioning
confidence: 99%